Production of bulk SiC parts by electrophoretic deposition from concentrated aqueous suspension. (January 2014) - Novak, S.; Ivekovič, A.; Hattori, Y.
Abstract : This paper reports on electrophoretic deposition of SiC bulk parts from highly loaded aqueous suspensions of submicron and nanosized powders. The effects of suspensions parameters ( ζ -potential, conductivity, solids content) and deposition parameters (voltage, current density, time) on quality of deposits were examined. It is presented that by using well defined suspension parameters high process stability is assured. For submicron powder, relatively high density was achieved, i.e. 60% TD (±2%), while for the nanosized SiC, the highest density was 42% TD (±2%). Mixing of powders did not result in density increase. Bulk >4 cm thick deposits were proved to have homogeneous density distribution, which is one of the advantages of electrophoretic deposition (EPD) process in comparison to other ceramic shape forming processes.